Effects of Integrated Extracts of Trigonella foenum-graecum and Asparagus racemosus on Hot Flash-like Symptoms in Ovariectomized Rats - Erten, Fusun; Er, Besir; Ozmen, Ramazan; Tokmak, Muhammed; Gokdere, Ebru; Orhan, Cemal; Şahin, Kazım (Mdpi, 2025)
Vasomotor symptoms, such as hot flashes (HFs), commonly affect women during menopause, leading to a reduced quality of life. The current study evaluates the combined effect of active components Asparagus racemosus (AR) and Trigonella foenum-graecum (TFG) in a single oral formulation (IAT) for alleviating menopausal symptoms in ovariectomized rats. Following bilateral ovariectomy, the animals were randomly assigned to nine groups: (1) Control, (2) Ovariectomy (OVX), (3) OVX+TA1 (TA: Combination of Trigonella and Asparagus; TFG 30 mg/kg + AR 30 mg/kg), (4) OVX+TA2 (TFG 30 mg/kg + AR 15 mg/kg), (5) OVX+TA3 (TFG 15 mg/kg + AR 30 mg/kg), (6) OVX+TA4 (TFG 40 mg/kg + AR 30 mg/kg), (7) OVX+TA5 (TFG 30 mg/kg + AR 40 mg/kg), (8) OVX+IAT1 (IAT: Integrated Asparagus and Trigonella; TFG+AR integrated extract, 30 mg/kg), and (9) OVX+IAT2 (TFG+AR integrated extract, 60 mg/kg). On the 8th day of treatment, tail and skin temperatures were recorded every 30 min for 24 h. Ovariectomized rats exhibited menopausal symptoms, such as hormonal imbalances and elevated skin temperature. Administration of AR, TFG, and IAT significantly decreased serum follicle-stimulating hormone (FSH), luteinizing hormone (LH), and cortisol while increasing estradiol, progesterone, and dopamine (p < 0.0001), effectively alleviating hot flash-like symptoms. Additionally, they mitigated ovariectomy-induced oxidative stress by lowering malondialdehyde (MDA) levels and restoring antioxidant enzyme activity. Ovariectomized rats exhibited increased expression of a proto-oncogene (c-FOS), gonadotropin-releasing hormone (GnRH), Kisspeptin, Neurokinin B (NKB), and Transient receptor potential vanilloid 1 (TRPV1), along with reduced expressing brain-derived neurotrophic factor (BDNF) levels, which were reversed by treatment, especially with the IAT2 combination. The AR and TFG combination, particularly in IAT formulations, showed strong potential in alleviating menopausal symptoms in ovariectomized rats. These findings suggest that the combination of AR and TFG extracts could be a natural alternative for managing postmenopausal symptoms by restoring reproductive hormone levels, regulating lipid profiles, and enhancing antioxidant defense systems.
Keywords: menopause; Trigonella foenum-graecum; Asparagus racemosus; menopausal symptoms; hormone therapy; vasomotor symptoms; ovariectomy